PENERAPAN VIDEO PEMBELAJARAN PENATAAN SANGGUL PUSUNG TAGEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK LABSCHOOL UNESA - Fatima Ayu Fernanda; Dewi Lutfiati; Sri Dwiyanti; Dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2025)
Updo hairstyling requires both theoretical understanding and practical skills, which are not easily mastered by students through verbal explanations alone. Therefore, a learning medium that can visually present the material and allow students to review it repeatedly is needed. The aim of this research is to enhance the academic achievements attained by the learners to their fullest potential on the topic of Penataan Sanggul Pusung Tagel by utilizing video media as a learning aid. This research applies a quantitative approach and uses a pre-experimental method with a one-group praujian-pascaujian design. The development of the instructional video was Grounded in the ADDIE framework, this process encompasses five sequential phases: Analysis, Design, Development, Execution, and Assessment. The research subjects were 30 eleventh-grade students of the Skin and Hair Beauty Department at SMK Labschool Unesa 1 Surabaya. The instruments used in this study included a media validation sheet, learning outcome tests for both cognitive and psychomotor domains, and a student response questionnaire. The validation results from five validators indicated that the instructional video falls under the